2019
DOI: 10.1016/j.jaci.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual allergen immunotherapy with a liquid birch pollen product in patients with seasonal allergic rhinoconjunctivitis with or without asthma

Abstract: Background: Sublingual allergen immunotherapy (SLIT) has been demonstrated to be both clinically efficacious and safe. However, in line with the current regulatory guidance from the European Medicines Agency, allergen immunotherapy (AIT) products must demonstrate their efficacy and safety in pivotal phase III trials for registration. Objective: We sought to investigate the efficacy and safety of sublingual high-dose liquid birch pollen extract (40,000 allergy units native [AUN]/mL) in adults with birch pollen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…as defined by the EAACI as standard primary endpoint for future (pivotal) trials in AIT 342 has been recently used recently in an increasing number of key trials in AIT. [343][344][345] However, further formal validation and amendments especially for the pediatric population are needed. 334,346 As another example, a further Task Force initiative aimed to provide clear clinically and aerobiologically justified definitions of pollen counts for onset, peak and duration of pollen seasons 347 and they have been confirmed to be robust 348 and clinically relevant as reflecting patients' symptom load in different countries in Europe in recent reports.…”
Section: B I Omark Er S Of the Epithelial Barriermentioning
confidence: 99%
“…as defined by the EAACI as standard primary endpoint for future (pivotal) trials in AIT 342 has been recently used recently in an increasing number of key trials in AIT. [343][344][345] However, further formal validation and amendments especially for the pediatric population are needed. 334,346 As another example, a further Task Force initiative aimed to provide clear clinically and aerobiologically justified definitions of pollen counts for onset, peak and duration of pollen seasons 347 and they have been confirmed to be robust 348 and clinically relevant as reflecting patients' symptom load in different countries in Europe in recent reports.…”
Section: B I Omark Er S Of the Epithelial Barriermentioning
confidence: 99%
“…AIT was previously shown to prevent the development of new sensitizations in HDM monosensitized children (161). The European Academy of Allergy and Clinical Immunology (EAACI) guidelines on AIT for allergic asthma and the new Global Initiative for Asthma (GINA) guidelines now include HDM SCIT (162). It is also worth noting that recent SLIT-based AIT trials in house dust mite (HDM) allergic asthma have shown some efficacy.…”
Section: Therapeutic Approaches To Hdm-induced Allergymentioning
confidence: 99%
“…Numerous clinical trials have demonstrated the benefit of allergen immunotherapy via both subcutaneous and sublingual tablet routes of administration for birch‐related allergic rhinoconjunctivitis . Novel epicutaneous patch delivery systems for birch AIT are also under development .…”
Section: Introductionmentioning
confidence: 99%